Associação melaço/ureia com silagem de sorgo, feno de soja perene e pastagem para novilhas - Garcia, José Américo; da Silva, Dirceu Jorge; Campos, Joaquim (Revista Ceres, 2025)
Twenty-four 21 month old Holstein x Zebu heifers weighing 295 kilos initialy were used to study the effects of feeding rations containing a mixture of molasses plus urea (9:1) with perennial soybean hay (Glicine Javanica L), sorghum silage or molassesgrass pasture (Melinis minutiflora Beauv) during the dry season.